Does Articular Disc Position Change Following Mandibular Setback Surgery? - Thamwatharsaree, Nathakarn; Panyarak, Wannakamon; Wantanajittikul, Kittichai; Yarach, Uten; Tachasuttirut, Kathawut (Journal of oral and maxillofacial surgery, 2024)
Maintaining condyle position following bilateral sagittal split ramus osteotomy (BSSO) is crucial to minimizing postoperative relapse. However, the impact of BSSO on the articular disc position remains inconclusive. This study aimed to investigate the changes in articular disc position following setback BSSO surgery. In this prospective cohort study, subjects with mandibular prognathism requiring setback BSSO were enrolled between August 2021 and June 2022 at the Oral and Maxillofacial Surgery Clinic, Faculty of Dentistry, Chiang Mai University, Thailand. Patients with surgical complications, loss of follow-up, or significant artifacts in their MR images were excluded. The predictor variable was time. The articular disc position was assessed at 3 time points, preoperatively (T0), 3 months postsurgery (T1), and 6 months postsurgery (T2). The primary and secondary outcome variables were the changes in articular disc position between T0-T2 and T0-T1, respectively. Articular disc position was coded as normal, anterior disc displacement with reduction (ADDwR), anterior disc displacement without reduction (ADDwoR), and anterior disc displacement without reduction and degenerative joint disease (ADDwoR + DJD). Covariate variables collected included age (years), sex (male or female), asymmetry (present or absent), surgical procedure (single jaw (BSSO) or bimaxillary surgery), and setback distance (millimeters). Friedman's test with 80% power and a significance level of 0.05 was employed. Pairwise comparisons were performed using the Dunn-Bonferroni posthoc test to identify statistically significant differences. The study included 16 subjects, 6 females and 10 males, with a total of 32 TMJs. Subjects had a mean age of 23.75 (4.57) years. The proportion of TMJs with normal disc position postoperatively increased from 3 (9.4%) to 19 (59.4%). Statistically significant differences were found in the changes in disc position over time (P < .001). Following setback BSSO, the articular discs underwent changes, with a majority of ADDwR cases transitioning to a normal position. Cases with ADDwoR also demonstrated disc reduction capability after surgery. The combined orthodontic treatment and setback BSSO appear to have an effect on articular disc position in skeleton class III patients.